Desmoglein 3 contributes to tumorigenicity of pancreatic ductal adenocarcinoma through activating Src–FAK signaling. Issue 3 (4th May 2021) - Abula, Yimamumaimaitijiang; Su, Yating; Tuniyazi, Dilixiati; Yi, Chao
ABSTRACT: Desmogleins (DSGs), with the ability to link adjacent cells, have been shown to participate in the development of malignancy. DSG3 was up-regulated in various cancers, including lung, head and neck, and esophagus squamous cell carcinoma, which contributed to the tumor progression. The role of DSG3 in pancreatic ductal adenocarcinoma (PDAC) still remains elusive. Here, the expression of DSG3 was found to be enhanced in pancreatic cancer cell lines in vitro . Functional assays showed that shRNA-mediated knockdown of DSG3 decreased cell viability of pancreatic cancer cells and retarded the cell proliferation, migration and invasion. However, pcDNA-mediated over-expression of DSG3 exhibited reversed effect on pancreatic cancer cell progression. In addition, the in vivo assay demonstrated that transfection of shDSG3 lentiviruses into pancreatic cancer cells repressed the tumorigenicity of PDAC after the cancer cells were transplanted into mice subcutaneously. Elevated DSG3 expression promoted the phosphorylation of Src (p-Src), focal adhesion kinase (p-FAK) and AKT (p-AKT) in vitro, while silence of DSG3 reduced the expression of p-Src, p-FAK and p-AKT both in vitro and in vivo . In conclusion, DSG3, as an oncogene, contributed to the tumorigenicity of PDAC through activating Src–FAK signaling.